2022
DOI: 10.1088/1755-1315/980/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

The potential solvent for tannin extraction as a feed additive made of coffee husk (Coffea canephora) using Soxhlet Method

Abstract: The purpose of this research was to determine the best of solvent for extracting tannins as a feed additive from coffee husks using the soxhlet method. The method used was quantitative with a completely randomized design experimental. The coffee husk used was a type of Robusta taken from the Kaliwates Region, Jember Regency, Indonesia. The material was the waste from the grinding of coffee cherries, namely the pericarp (parchment, pectin layer, pulp, and outer husk). This research consisted of 3 treatments (P1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
1
8
0
2
Order By: Relevance
“…Polyphenols are recognized as beneficial phytochemicals for human health; nevertheless, these compounds can interact with proteins, carbohydrates, lipids, and other food matrix components, which might significantly affect the nutritional and nutraceutical potential of fortified products ( 248 251 ). For example, tannins might develop tannin–protein complexes, which reduces their antioxidant ability ( 44 , 45 ). Because of the complexity of polyphenol interactions within the food matrix ( 252 ), it is important that each food matrix be assessed individually regarding its interacting phenolic compounds throughout the development of functional food enriched with phenolic-rich plant extract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyphenols are recognized as beneficial phytochemicals for human health; nevertheless, these compounds can interact with proteins, carbohydrates, lipids, and other food matrix components, which might significantly affect the nutritional and nutraceutical potential of fortified products ( 248 251 ). For example, tannins might develop tannin–protein complexes, which reduces their antioxidant ability ( 44 , 45 ). Because of the complexity of polyphenol interactions within the food matrix ( 252 ), it is important that each food matrix be assessed individually regarding its interacting phenolic compounds throughout the development of functional food enriched with phenolic-rich plant extract.…”
Section: Discussionmentioning
confidence: 99%
“…For example, acidified water or organic solvent (e.g., ethanol or methanol) are effectively used to prepare plant extract rich in anthocyanins ( 43 ). Tannins are phenolic compounds with high molecular weights that form colloids when dissolved in water ( 44 , 45 ). Furthermore, the solubility of tannins is variable, and depending on the target molecules, solvents with different polarities like water, ethanol, methanol, and acetone, as well as their aqueous solutions, might be used for extraction ( 7 , 44 , 45 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary study showed that the addition of 9 g of tannin additives per kg of grass was able to maintain the protein nutrient content from microbial degradation during the ensilage process. The extract method used in the preliminary study was Soxhlet extraction using ethanol as a solvent [4]. The obstacle faced was if we are going to produce on a large scale/business scale as in the general ruminant business, such as sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Solvents usually used in the maceration process include methanol, ethanol, acetone, sodium hydroxide, and liquid ions (Das et al, 2020). Ethanol solvents are more effective in producing higher total tannins than methanol and acetone solvents (Kusuma et al, 2022).…”
Section: Introductionmentioning
confidence: 99%